2009
DOI: 10.1177/0269216309346541
|View full text |Cite
|
Sign up to set email alerts
|

Making sure services deliver for people with advanced heart failure: a longitudinal qualitative study of patients, family carers, and health professionals

Abstract: The objective of this study was to evaluate the key components of services for people with advanced heart failure from multiple perspectives and recommend how care might be delivered in line with UK policies on long-term conditions, palliative and end-of-life care. Serial interviews were conducted over 2 years with patients, case-linked family carers and professionals (n =162); followed by four focus groups involving patients, carers and key professionals (n =32). There were 36 patients with advanced heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 25 publications
1
74
0
11
Order By: Relevance
“…111 In recent years, longitudinal qualitative research has been used in a number of health-related areas to generate rich data and a deeper understanding of people's perspectives and experiences and how and why these may change over time in order to improve practice. [112][113][114][115] Rather than comparing findings at a number of distinct moments, longitudinal qualitative research is concerned with the comparison of different, continuous processes of change. The benefits of the longitudinal design will be that it will permit the same participants to be involved in identifying practice challenges and solutions, in developing methods for how alerts and recommendations can be best delivered for action, and for examining and reflecting on the effects with regard to practice change as well as system evaluation and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…111 In recent years, longitudinal qualitative research has been used in a number of health-related areas to generate rich data and a deeper understanding of people's perspectives and experiences and how and why these may change over time in order to improve practice. [112][113][114][115] Rather than comparing findings at a number of distinct moments, longitudinal qualitative research is concerned with the comparison of different, continuous processes of change. The benefits of the longitudinal design will be that it will permit the same participants to be involved in identifying practice challenges and solutions, in developing methods for how alerts and recommendations can be best delivered for action, and for examining and reflecting on the effects with regard to practice change as well as system evaluation and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…286 Additional barriers to the provision of palliative care services identified by healthcare providers included uncertainty about end of life because of its unpredictable trajectory, lack of need for end-of-life discussions in patients in New York Heart Association class II to III HF, and lack of time and resources to initiate discussions. [286][287][288] In qualitative reports, patients and families had misperceptions about being separated from familiar, trusted healthcare providers and not being hospitalized once they committed to palliative care. Accordingly, it has been suggested that healthcare providers need to introduce palliative care as a philosophy of care rather than a strategy used at end of life.…”
Section: Palliative Care Use and Perceptions In Cardiovascular Practicementioning
confidence: 99%
“…31 Involving family caregivers, strongly advocated by participants, is generally not a part of contemporary HF care or disease management programs, which remain focused on the individual patient. Participants prefer providers familiar with patients' heart condition are involved in addressing palliative care needs.…”
Section: Implications For Hf Palliative Care Service Provisionmentioning
confidence: 99%